2014
DOI: 10.1007/s40477-014-0097-2
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the malignant peripheral nerve sheath tumour with emphasis οn ultrasonography: correlation with MRI

Abstract: Malignant peripheral nerve sheath tumours affect 0.001 % of the population. The epithelioid subtype accounts for only 5 % of them. We herein present a patient with a palpable mass on the left calf, which was investigated by ultrasonography, ultrasonographically guided fine-needle biopsy and MRI. Ultrasonography estimated the size of the tumour and evaluated its echotexture. Doppler technique detected characteristic corkscrew-type blood vessel entering in the upper pole of the mass. T1-weighted, fat-suppression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Redzepagic et al [ 5 ] reported a case in the breast, which is a rare location for MPNST. Rafailidis et al [ 6 ] believe that MPNST typically affects major nerve trunks like the sciatic nerve, the brachial plexus, and the sacral plexus. However, in our group, except for two retroperitoneal tumors, all MPNSTs developed superficially and had no direct connection with these major nerve trunks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Redzepagic et al [ 5 ] reported a case in the breast, which is a rare location for MPNST. Rafailidis et al [ 6 ] believe that MPNST typically affects major nerve trunks like the sciatic nerve, the brachial plexus, and the sacral plexus. However, in our group, except for two retroperitoneal tumors, all MPNSTs developed superficially and had no direct connection with these major nerve trunks.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our group, except for two retroperitoneal tumors, all MPNSTs developed superficially and had no direct connection with these major nerve trunks. MPNST usually affects patients in 20 to 50 years old, without gender predilection [ 6 ]. It occurs more often in association with NF-1 and leads to poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…73 They commonly involve major nerves and nerve trunks such as the sciatic, sacral, or brachial plexus. 75 Cranial nerve involvement and intraosseous lesions are rare. 64,76,77 Benign Malignant MPNST should be suspected when there is a rapid increase in the size of a stable neurofibroma, development of pain, or neurology.…”
Section: Malignant Peripheral Nerve Sheath Tumormentioning
confidence: 99%
“…Ultrasound and computed tomography (CT) can also be of value in select patients and may be used for image-guided biopsies. 12 Furthermore, bone scintigraphy may be useful to evaluate for osseous involvement. 13 Over recent years, PET has been gaining increasing traction in the assessment of musculoskeletal tumors.…”
Section: Introductionmentioning
confidence: 99%